PERSEPSI WISATAWAN TERHADAP FASILITAS WISATA DI PUSAT LATIHAN GAJAH TAMAN NASIONAL WAY KAMBAS - shinta dewi marcelina; Indra Gumay Febryano; Agus Setiawan; Slamet Budi Yuwono (Forestry Study Program University Of Mataram, 2018)
The growth of tourism is affected by the level of satisfication from the visitors towords the existence of tourism facilities. The aim of this research is to know the visitors perspective towards the tourism facilities at Elephant Training Center of Way Kambas National Park. The data taking can be done by doing interviews, observation and literatures. The collected data will be analyzed descriptively based on physics, cleaniness and comfort condition. The result of research shows that the visitors perception towards the tourism facilities is enough. This is not apart from the condition of facilities that are less well meintained and even damaged, such as toilets, bins, attractions arena and playground; although the qality and quntity is sufficient for the needs of tourist. The national park party needs to add the amount and improve the facilities so it can support the management of the area and improve the amoun of visitors.